Current‐aligned dewatering sheets and 'enhanced' primary current lineation in turbidite sandstones of the Marnoso‐arenacea Formation. Issue 5 (28th April 2016) - Amy, Lawrence A.; Talling, Peter J.; Sumner, Esther J.; Malgesini, Giuseppe
Abstract: Turbidite sandstones of the Miocene Marnoso‐arenacea Formation (northern Apennines, Italy) display centimetre to decimetre long, straight to gently curved, 0·5 to 2·0 cm regularly spaced lineations on depositional (stratification) planes. Sometimes these lineations are the planform expression of sheet structures seen as millimetre to centimetre long vertical 'pillars' in profile. Both occur in the middle and upper parts of medium‐grained and fine‐grained sandstone beds composed of crude to well‐defined stratified facies (including corrugated, hummocky‐like, convolute, dish‐structured and dune stratification) and are aligned sub‐parallel to palaeoflow direction as determined from sole marks often in the same beds. Outcrops lack a tectonic‐related fabric and therefore these structures may be confidently interpreted to be sedimentary in origin. Lineations resemble primary current lineations formed by the action of turbulence during bedload transport under upper stage plane bed conditions. However, they typically display a larger spacing and micro‐topography compared to classic primary current lineations and are not associated with planar‐parallel, finely laminated sandstones. This type of 'enhanced lineation' is interpreted to develop by the same process as primary current lineations, but under relatively high near‐bed sediment concentrations and suspended load fallout rates, as supported by laboratory experiments and host facies characteristics. Sheets are interpreted to be dewatering structures and their alignment to palaeoflow (only noted in several other outcrops previously) inferred to be a function of vertical water‐escape following the primary depositional grain fabric. For the Marnoso‐arenacea beds, sheet orientation may be linked genetically to the enhanced primary current lineation structures. Current‐aligned lineation and sheet structures can be used as palaeoflow indicators, although the directional significance of sheets needs to be independently confirmed. These indicators also aid the interpretation of dewatered sandstones, suggesting sedimentation under a traction‐dominated depositional flow – with a discrete interface between the aggrading deposit and the flow – as opposed to under higher concentration grain or hindered‐settling dominated regimes.